Tính \(\sqrt{2\sqrt{3\sqrt{4...\sqrt{2018}}}}\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(y=\sqrt{\frac{x^2}{4}+\sqrt{x^2-4}}+\sqrt{\frac{x^2}{4}-\sqrt{x^2-4}}\) Điều kiện: \(x\ge2\)
\(\Rightarrow2y=2.\sqrt{\frac{x^2}{4}+\sqrt{x^2-4}}+2.\sqrt{\frac{x^2}{4}-\sqrt{x^2-4}}\)
\(=\sqrt{x^2+4\sqrt{x^2-4}}+\sqrt{x^2-4\sqrt{x^2-4}}\)
\(=\sqrt{x^2-4+4\sqrt{x^2-4}+4}+\sqrt{x^2-4-4\sqrt{x^2-4}+4}\)
\(=\sqrt{\left(\sqrt{x^2-4}+2\right)^2}+\sqrt{\left(\sqrt{x^2-4}-2\right)^2}\)
\(=\left|\sqrt{x^2-4}+2\right|+\left|\sqrt{x^2-4}-2\right|\)
\(=\sqrt{x^2-4}+2+\left|\sqrt{x^2-4}-2\right|\)(1)
TH1: \(\sqrt{x^2-4}-2\ge0\Rightarrow\sqrt{x^2-4}\ge2\Rightarrow x^2-4\ge4\Rightarrow x\ge2\sqrt{2}\).Ta có:
\(\left(1\right)=\sqrt{x^2-4}+2+\sqrt{x^2-4}-2=2\sqrt{x^2-4}\)
Do \(x\ge2\sqrt{2}\Rightarrow2\sqrt{x^2-4}\ge2\sqrt{\left(2\sqrt{2}\right)^2-4}=4\)
TH2: \(\sqrt{x^2-4}-2< 0\Rightarrow\sqrt{x^2-4}< 2\Rightarrow x^2-4< 4\Rightarrow x^2< 8\Rightarrow2\le x< 2\sqrt{2}\).Ta có:
\(\left(1\right)=\sqrt{x^2-4}+2-\sqrt{x^2-4}+2=4\)
Vậy GTNN của y bằng 4.
Dấu "=" xảy ra khi \(2\le x\le2\sqrt{2}\)
\(\forall n\inℕ^∗\)ta có:
\(\frac{1}{\left(n+1\right)\sqrt{n}+n\sqrt{n+1}}=\frac{\left(n+1\right)\sqrt{n}-n\sqrt{n+1}}{\left(n+1\right)^2n-n^2\left(n+1\right)}\)
\(=\frac{\left(n+1\right)\sqrt{n}-n\sqrt{n+1}}{n\left(n+1\right)}=\frac{1}{\sqrt{n}}-\frac{1}{\sqrt{n+1}}\) (*)
Thay n=1; n=2; n=3; .....; n=2004 Ta có:
\(S=\frac{1}{\sqrt{1}}-\frac{1}{\sqrt{2}}+\frac{1}{\sqrt{2}}-\frac{1}{\sqrt{3}}+...+\frac{1}{\sqrt{2004}}-\frac{1}{\sqrt{2005}}\)
\(=1-\frac{1}{\sqrt{2005}}\)
\(A=\sqrt{2+\sqrt{3}}-\sqrt{2-\sqrt{3}}\)
=> \(\sqrt{2}.A=\sqrt{4+2\sqrt{3}}-\sqrt{4-2\sqrt{3}}\)
\(=\sqrt{\left(\sqrt{3}+1\right)^2}-\sqrt{\left(\sqrt{3}-1\right)^2}\)
\(=\sqrt{3}+1-\left(\sqrt{3}-1\right)=2\)
=> \(A=\sqrt{2}\)
\(=\frac{\sqrt{4+2\sqrt{3}}-\sqrt{4-2\sqrt{3}}}{\sqrt{2}}.\)
\(=\frac{\sqrt{\left(\sqrt{3}+1\right)^2}-\sqrt{\left(\sqrt{3}-1\right)^2}}{\sqrt{2}}\)
\(=\frac{\left|\sqrt{3}+1\right|-\left|\sqrt{3}-1\right|}{\sqrt{2}}\)
\(=\frac{\sqrt{3}+1-\sqrt{3}+1}{\sqrt{2}}=\frac{2}{\sqrt{2}}=\sqrt{2}\)